The Urban crisis : can grass-roots groups succeed where government has failed? - Daly, John Charles; Duncan, Sydney; American Enterprise Institute for Public Policy Research (Washington, D.C. : AEI, 1981)
This pamphlet contains the edited transcript of one of a series of AEI forums. A recent Twentieth Century Fund task force stressed that although males between the ages of thirteen and twenty constitute only 9 percent of the total population, they account for more than half of all property crime arrests and for more than 33 percent of offenses involving violence.The purpose of this forum therefore, is to examine a few instances of success amid all the failure: local groups and individuals who have solved many of the problems that have defied solution by large social service institutions.
ne 08/11/2019
Loans
Keywords: Urban policy